Multidisciplinary impact – the arts join informal STEM programs. (7th May 2019) - Tretola, Betsy; Coupey, Eloise; Meamber, Laurie
Abstract : Purpose: Middle school participants in the USA attending an on-campus university informal science program indicate an increase in interest toward careers and disciplines in STEM or STEAM (science, technology, engineering and mathematics and the arts). Parents or guardians confirm the change. The paper aims to discuss this issue. Design/methodology/approach: Participants attended "inquiry-based" lectures by scientists and "hands-on" activities conducted by volunteers on campus at a public university over four months, four Saturdays. Participants completed surveys before each lecture and guardians completed surveys afterwards. Findings: Interest increased significantly according to paired samples t -tests for each STEM discipline for students who reported low interest on the initial pre-lecture survey. There was a significant linear improvement in interests in engineering using a repeated measures general linear model. Guardians or parents reported that they observed a higher interest in STEM disciplines resulting in more technical-related interaction among peers and within the family. Social implications: Findings support STEM with arts "out-of-school" programs sponsored by museums, corporations, government, higher education and others. Inclusion of the "hands-on" activities, some with arts content, to the science and technical learning appears to spark enthusiasm. Originality/value: The value is multidisciplinary. The theory of reasoned action from social psychology, sociology, along with related research in science education and the arts are synthesized. Informal extracurricular experiences sustained and improved interests in the disciplines and careers on which the formal educational career pipeline can build.